Abnormal Endogenous Repression of GA Signaling in a Seedless Table Grape Cultivar with High Berry Growth Response to GA Application - Acheampong, Atiako K.; Zheng, Chuanlin; Halaly, Tamar; Giacomelli, Lisa; Takebayashi, Yumiko; Jikumaru, Yusuke; Kamiya, Yuji; Lichter, Amnon; Or, Etti (Frontiers in Plant Science, 2017)
Gibberellin (GA) application is routinely used in the table grape industry to increase berry size and cluster length. Although grapevine cultivars show a wide range of growth responsiveness to GA3 application, the reasons for these differences is unclear. To shed light on this issue, two commercial grapevine cultivars with contrasting berry response to GA were selected for comparative analysis, in which we tested if the differences in response: 1) is organ-specific or cultivar-related; 2) will be reflected in qualitative/quantitative differences in transcripts/proteins of central components of GA metabolism and signaling and levels of GA metabolites. Our results showed that in addition to the high response of its berries to GA, internodes and rachis of cv. Black finger (BF) presented a greater growth response compared to that of cv. Spring blush (SB). In agreement, the results exposed significant quantitative differences in GA signaling components in several organs of both cultivars. Exceptionally higher level of all three functional VvDELLA proteins was recorded in young BF organs, accompanied by elevated VvGID1 expression and lower VvSLY1b transcripts. Absence of seed traces, low endogenous GA quantities and lower expression of VvGA20ox4 and VvGA3ox3 were also recorded in berries of BF. Our results raise the hypothesis that, in young organs of BF, low expression of VvSLY1b may be responsible for the massive accumulation of VvDELLA proteins, which then leads to elevated VvGID1 levels. This integrated analysis suggests causal relationship between endogenous mechanisms leading to anomalous GA signaling repression in BF, manifested by high quantities of VvDELLA proteins, and greater growth response to GA application.